The early writings of Francois Hemsterhuis, 1762-1773 - Hemsterhuis, François, 1721-1790 (The Edinburgh Edition of the Complete Philosophical Works of François Hemsterhuis ;, 2022)
This critical edition translates Hemsterhuis' 'Letter on an Antique Gemstone', 'Letter on Sculpture', 'Letter on Desires', 'Letter on Man and his Relations' and 'Philosophical Description of the Character of the Late Mr F. Fagel' into English for the first time. Three introductions explore these texts' influence and significance.